Pendidikan Life Skill dalam Meningkatkan Kemandirian Santri di Pondok Pesantren Nurul Hidayah Kebumen - Ahmad Syu'bi Alwi; Makhrur Adam Maulana; Agus Nur Soleh (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The objectives of this study are todescribe the actualization of life skills education in increasing the independence of students applied by the Nurul Hidayah Islamic Boarding School Kebumen and describe the methods of life skills education in increasing the independence of students at the Nurul Hidayah Islamic Boarding School Kebumen. This research is a type of field research, where the authors collect data by conducting in-depth studies in the form of interviews with caregivers, Pondok Lurah and Head of Field Coordination as key informants (providers of key information) as well as observing phenomena that occur and documenting the data. Then the data was analyzed using a qualitative descriptive method which was intended to describe a factual situation. The collected data were analyzed using reduction, presentation, and data verification. The results of this study conclude that the actualization of life skills education in increasing the independence of students at the Nurul Hidayah Islamic Boarding School Kebumen is good, where life skills education activities include planning, implementation and evaluation. Furthermore, in the implementation of life skills education activities for students, the students do not leave their obligations as a student, namely reading the Koran and participating in all cottage activities. The method used in life skills education in increasing the independence of students at the Nurul Hidayah Islamic Boarding School Kebumen is the On The Job Training model in the form of coaching or guidance. The On the Job Training model means that the students are trained to learn jobs in the pesantren business unit and they are working on it while doing it. While coaching is the coach going into the field while explaining and practicing slowly how to do the job correctly.